Interrelation between hypoxic liver injury and Killip classification in ST-segment elevation myocardial infarction patients - Choi, Seong Huan; Jang, Ji-Hun; Kim, Dae-Young; Suh, Young Ju; Baek, Yong-Soo; Shin, Sung-Hee; Woo, Seong-Ill; Kim, Dae-Hyeok; Moon, Jeonggeun; Suh, Jon; Kang, WoongChol; Park, Sang-Don; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHypoxic liver injury (HLI) and Killip classification are poor prognostic factors in patients with ST-segment elevation myocardial infarction (STEMI). This study investigates the interrelationship between hypoxic liver injury (HLI) and Killip classification.Method and resultsA total of 1,537 STEMI patients who underwent percutaneous coronary intervention (PCI) from 2007 to 2014 at four tertiary hospitals in the Incheon-Bucheon province were enrolled in this study. The patients were divided into four groups based on their Killip classification at presentation in the emergency room (ER). HLI was defined as a ≥2-fold increase in serum aspartate transaminase (AST). The incidence of HLI showed incremental tendency with respect to the Killip classification (19.5%, 19.4%, 34.6%, and 37.8%, respectively; p < 0.001). Left ventricular ejection fraction (LVEF) was below 45% in symptomatic, overt heart failure patients (Killip class II, III, and IV). Both initial and peak AST levels increased in accordance with Killip classification along with cardiac biomarkers. In-hospital mortality was directly related to Killip classification (2.3%, 7.3%, 16.3%, 29.2%) with statistical significance. Univariate and multivariate Cox regression analysis showed that the presence of HLI and combined Killip classification III and IV were poor prognostic factors, even after adjusting for conventional clinical risk factors. Receiver operating characteristic (ROC) analysis showed that combination of HLI and Killip classification was the most sensitive predictor of mortality (AUC 0.832, 95% CI 0.78–0.882). Kaplan–Meier curve showed that patients with HLI and Killip class (III and IV) had the lowest event-free survival regarding in-hospital mortality and major cardiovascular and cerebrovascular events.ConclusionsThe presence of HLI and Killip classification were directly related to worse prognosis in STEMI patients. Early recognition of HLI and accurate assessment of Killip classification is warranted for effective management of STEMI.